Disaggregated accruals and prediction of future cash flows: An effect of global financial crisis 2008-09 - Rai, I. H.; Noor Saadah,; Jaspal, S. J. S. *; Hanzla, M. (ITJEMAST, 2019)
The objective of the study was to find out the relationship among further extended disaggregated accruals and forecast of imminent cash flows in the developing market of Pakistan during the global financial crisis 2008-09 and pre and post-global financial crisis. Panel data of 8154 firms-years observations were analyzed through panel least square. Hausman and redundant fixed effect tests suggested a fixed-effects model. The stationarity of variables was tested and correlation and regression analysis were conducted. The association of variables during the financial crisis and pre and post-financial crisis was controlled through dummy variables. The study finds that disaggregated accruals as extended components of disaggregated accruals regressed the estimate of imminent cash flows significantly except financial assets. Additionally, results were not affected throughout the global financial crisis 2008-09 for emerging markets of Pakistan but the prediction of future cash flows was affected pre and post-financial crisis 2008-09. Furthermore, the association between the pre-financial crisis and forecast of imminent cash flows was negative but found positive in the post-financial crisis.